Structural Proteomics High-Throughput Methods - Kobe, Bostjan; Guss, Mitchell; Huber, Thomas; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2008)
Structural genomics is a newly emerging field that has arisen following the successful footsteps of the major sequencing efforts generally bundled under the heading "genomics". In Structural Proteomics: High Throughput Methods, readers are provided with a current view of all aspects of the 'pipeline' that takes protein targets to structures and how these have been optimized. This volume includes chapters describing in-depth the individual steps in the Structural Genomics pipeline, as well as overviews of individual Structural Genomics initiatives. Topics include Target Selection for structural genomics, Protein structure modeling, High-throughput cloning, Mass Spectrometry modeling. Structural Proteomics: High Throughput Methods, encourages its readers to access further details on the methodologies in on-line resources as well as in cited literature making it an invaluable resource. Most methods in this important book are as amenable to small laboratories as to large consortia, and do not require major investments in facilities. This essential volume provides insight into the diversity of approaches adopted by different laboratories and proves that 'high throughput' is really the defining characteristic of structural genomics.
Protein Target Selection, Bioinformatic Approaches, and Data Management -- Target Selection for Structural Genomics: An Overview -- A General Target Selection Method for Crystallographic Proteomics -- Target Selection: Triage in the Structural Genomics Battlefield -- Data Management in Structural Genomics: An Overview -- Data Deposition and Annotation at the Worldwide Protein Data Bank -- Prediction of Protein Disorder -- Protein Domain Prediction -- Protein Structure Modeling with MODELLER -- Protein Production -- High Throughput Cloning with Restriction Enzymes -- Automated Recombinant Protein Expression Screening in Escherichia coli -- From No Expression to High-Level Soluble Expression in Escherichia coli by Screening a Library of the Target Proteins with Randomized N-Termini -- Application of High-Throughput Methodologies to the Expression of Recombinant Proteins in E. coli -- A High Throughput Platform for Eukaryotic Genes -- High Throughput Production of Recombinant Human Proteins for Crystallography -- Assembly of Protein Complexes by Coexpression in Prokaryotic and Eukaryotic Hosts: an Overview -- Cell-Free Protein Synthesis for Analysis by NMR Spectroscopy -- A Medium or High Throughput Protein Refolding Assay -- Structural Proteomics of Membrane Proteins: a Survey of Published Techniques and Design of a Rational High Throughput Strategy -- Biophysical and Functional Characterization of Proteins -- Methods for Protein Characterization by Mass Spectrometry, Thermal Shift (ThermoFluor) Assay, and Multiangle or Static Light Scattering -- High Throughput Methods for Analyzing Transition Metals in Proteins on a Microgram ScaleHigh Throughput Methods for Analyzing Transition Metals in Proteins on a Microgram Scale -- High Throughput Screening of Purified Proteins for Enzymatic Activity -- Structural Characterization of Proteins -- Strategies for Improving Crystallization Success Rates -- Protein Crystallization in Restricted Geometry: Advancing Old Ideas for Modern Times in Structural Proteomics -- Fluorescence Approaches to Growing Macromolecule Crystals -- Efficient Macromolecular Crystallization Using Microfluidics and Randomized Design of Screening Reagents -- Increasing Protein Crystallization Screening Success with Heterogeneous Nucleating Agents -- High Throughput pH Optimization of Protein Crystallization -- Automated Structure Solution with the PHENIX Suite -- NMR Screening for Rapid Protein Characterization in Structural Proteomics -- Microcoil NMR Spectroscopy: a Novel Tool for Biological High Throughput NMR Spectroscopy -- Protein Structure Determination Using a Combination of Cross-linking, Mass Spectrometry, and Molecular Modeling -- Structural Proteomics Initiatives Overviews -- Structural Genomics of Minimal Organisms: Pipeline and Results -- Structural Genomics of Pathogenic Protozoa: an Overview -- High Throughput Crystallography at SGC Toronto: an Overview -- The Structural Biology and Genomics Platform in Strasbourg: an Overview -- Bacterial Structural Genomics Initiative: Overview of Methods and Technologies Applied to the Process of Structure Determination -- High Throughput Protein Production and Crystallization at NYSGXRC -- Overview of the Pipeline for Structural and Functional Characterization of Macrophage Proteins at the University of Queensland -- Structural Genomics of the Bacterial Mobile Metagenome: an Overview.
Keywords: Life sciences; Proteomics; Proteins; Bioinformatics; Cell biology; Microbial genetics; Microbial genomics; Life Sciences; Protein Science; Proteomics; Microbial Genetics and Genomics; Bioinformatics; Cell Biology; Electronic books